2002
DOI: 10.1212/wnl.58.3.354
|View full text |Cite
|
Sign up to set email alerts
|

Cluster headache

Abstract: Background: Cluster headache, when compared with migraine or tension-type headache, is an uncommon form of primary neurovascular headache. However, with a prevalence of approximately 0.1% and a lengthy history of disabling and distressing episodic pain, cluster headache is an important neurologic problem. Methods: Patients (n ϭ 230) were recruited from our specialist clinic (24%) or from support groups (76%). All patients had a detailed history taken by at least two physicians and were assigned diagnoses accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

72
553
24
20

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(673 citation statements)
references
References 72 publications
(50 reference statements)
72
553
24
20
Order By: Relevance
“…Yet, for rs1800759 the mutant allele seems to be less common in the Italian cohorts (31.0%–33.7%) compared with our Swedish cohort (42.3%). From our questionnaire data, 56.2% of the patients reported that alcohol may trigger an attack which corresponds to what other groups have reported (52%–63%) 7, 8, 9. When performing a statistical analysis for control individuals and CH patients reporting alcohol as a trigger factor, there were no significant differences in the genotypes of the two groups for either SNP.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Yet, for rs1800759 the mutant allele seems to be less common in the Italian cohorts (31.0%–33.7%) compared with our Swedish cohort (42.3%). From our questionnaire data, 56.2% of the patients reported that alcohol may trigger an attack which corresponds to what other groups have reported (52%–63%) 7, 8, 9. When performing a statistical analysis for control individuals and CH patients reporting alcohol as a trigger factor, there were no significant differences in the genotypes of the two groups for either SNP.…”
Section: Discussionsupporting
confidence: 83%
“…However, already in 1941 Bayard Horton observed that alcohol may elicit an attack in CH patients during the active phase 5. More recently, it has been reported that 52%‐79% of the patients experience alcohol to trigger an attack when in a bout 6, 7, 8, 9. However, the study reporting a frequency of 79% included only male patients with episodic CH 6.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the two patients who began complaining of CH symptoms at an uncommon age (11 and 70 years) are noteworthy, although similar cases have been previously reported 19 . The proportion of episodic and chronic patterns of CH in this sample (approximately 4:1) is also concordant with most studies 20 . The high number of cases matching the criteria for SUNCT in this study is unexpected, as this type of headache is described as very uncommon.…”
Section: Discussionsupporting
confidence: 91%
“…In some patients, the attacks occur at roughly the same time of the day every day, and in other clusters occur in the same period every year. 37 Permanent remission is seen, but after 15 years with the disease, 80% of patients still have attacks. However, about 10-15% of patients have chronic symptoms without remissions.…”
Section: Clinical Manifestationmentioning
confidence: 99%